PHOSPHATE SOLUBILIZING MICROBES: AN EFFECTIVE AND ALTERNATIVE APPROACH AS BIOFERTILIZERS - Anand, Kumar; Kumari, Baby; Mallick, M. A. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
It is undoubtedly clear that phosphorus is the second most important nutrient after nitrogen required for growth of plants. It is an essential element in all living systems. Hardly 1%-2% of phosphorous is supplied to other parts of the plants. Plants acquire phosphorus from soil solution in the form of phosphate anion. It is the least mobile element in plant and soil in comparison to other macronutrients. It remains in a precipitated form in the soil as mono or orthophosphate or is absorbed by Fe or Al oxides through legend exchange. Generally, the phosphate solubilizing microorganisms (PSM) play a very important role in phosphorus nutrition by exchanging its availability to plants through release from inorganic and organic soil phosphorus pools by solubilization and mineralization. The main mechanism in the soil for mineral phosphate solubilization is by lowering the soil pH by the microbial production of organic acids and mineralization of organic phosphorus by acid phosphates. To fulfill the phosphorous demand of plant, an additional source of phosphorous is applied to plants in the form of chemical fertilizers. One of the most common forms of phosphate is fertilizers in the form of rock phosphate or superphosphate. It is not suggested to apply these phosphates directly to soil as there are so many environmental problems. Hence, biofertilizers or microbial inoculants are used as an alternate source, which are both economic as well as eco-friendly. Â